If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1.4(x + -8) + 12 = 0.6(x + -2) + 1 Reorder the terms: -1.4(-8 + x) + 12 = 0.6(x + -2) + 1 (-8 * -1.4 + x * -1.4) + 12 = 0.6(x + -2) + 1 (11.2 + -1.4x) + 12 = 0.6(x + -2) + 1 Reorder the terms: 11.2 + 12 + -1.4x = 0.6(x + -2) + 1 Combine like terms: 11.2 + 12 = 23.2 23.2 + -1.4x = 0.6(x + -2) + 1 Reorder the terms: 23.2 + -1.4x = 0.6(-2 + x) + 1 23.2 + -1.4x = (-2 * 0.6 + x * 0.6) + 1 23.2 + -1.4x = (-1.2 + 0.6x) + 1 Reorder the terms: 23.2 + -1.4x = -1.2 + 1 + 0.6x Combine like terms: -1.2 + 1 = -0.2 23.2 + -1.4x = -0.2 + 0.6x Solving 23.2 + -1.4x = -0.2 + 0.6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6x' to each side of the equation. 23.2 + -1.4x + -0.6x = -0.2 + 0.6x + -0.6x Combine like terms: -1.4x + -0.6x = -2x 23.2 + -2x = -0.2 + 0.6x + -0.6x Combine like terms: 0.6x + -0.6x = 0.0 23.2 + -2x = -0.2 + 0.0 23.2 + -2x = -0.2 Add '-23.2' to each side of the equation. 23.2 + -23.2 + -2x = -0.2 + -23.2 Combine like terms: 23.2 + -23.2 = 0.0 0.0 + -2x = -0.2 + -23.2 -2x = -0.2 + -23.2 Combine like terms: -0.2 + -23.2 = -23.4 -2x = -23.4 Divide each side by '-2'. x = 11.7 Simplifying x = 11.7
| 4x+5y=44 | | .183=x+(x-.12)*(1.5)*(.65) | | 1.3x=5.9 | | (6x-22)+(8x+34)=180 | | 7x-1/x-1 | | -(6m+1)=-8+15 | | -3(-3x-3)=-4x-4 | | 7x+-14=5x+10 | | -0.25(-20x+12)=-13 | | x+x*y=0.5 | | x+0.1x=0.67 | | 6(a+4)=4(2a+3) | | (5x+38)+(12x-28)=180 | | x^2+2x+40=40 | | 4p-14+2p+3=14p-10+2p-21 | | 2x=-5x+77 | | 3(x-3)+9=2.1(x+2)-4 | | 4(8-15)=y-2 | | 5x+39=7x+15 | | 4(8-5)=y-2 | | 5(k-3)=12k-6-11k+15 | | 7w=87w | | -9+17=m-5 | | 6j+15-8j+10=3(3j+1) | | -3/7(y-14)-1/21y | | 3(2x+4)=4(-x)+6 | | -4.5x=-11.25 | | 7p^2-22=-8p | | 4x^2-y^2-4x+1=0 | | 5(x-12)+x=180 | | sinx=0.785 | | 3h+1+h+13=2(3h-4) |